A Critical Investigation of English Subject Teaching at Two Types of Madrasas in Bangladesh - Golam, Azam MD (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractThis study aims to survey the secular subject, teaching of English, and learning in Qawmi Madrasas at grade 8 and Alia Madrasas in Bangladesh. Ethno-methodological surveys have been conducted in 2018 of the Southern region of Bangladesh, particularly among the students, teachers, and principals of eight Qawmi madrasas and five Alia madrasas. Findings revealed that Qawmi Madrasas do not have a conducive English learning environment for grade 8 level, class duration and schedule, teachers' salaries, as well as resources, found inadequate as opposed to the Alia religious schools. Unlike Qawmi Madrasas (Independent Islamic seminaries), Alia Madrasas (reformed religious schools) have so far, the privileges. Interviewees reported the immediate need for teacher training in English language learning for Qawmi religious schools. Moreover, students in the Qawmi schools also claimed that the resources used in the classroom, such as English textbooks should be employed more effectively. This research also found that internal and external factors forced them to include the secular subject, English in particular in their syllabi. Previous studies have focused mainly on religious schools through a sociological lens. However, this study addresses the secular subject, English teaching at unsecular religious schools in Bangladesh; hence, it provides values for avid readers, researchers and those who are involved in future studies of this country.AbstrakPenelitian ini bertujuan untuk mensurvei mata pelajaran sekuler, pengajaran bahasa Inggris, dan pembelajaran di Madrasah Qawmi kelas 8 dan Madrasah Alia di Bangladesh. Survei etno-metodologi telah dilakukan pada tahun 2018 di wilayah selatan Bangladesh, khususnya di antara siswa, guru, dan kepala sekolah dari delapan madrasah Qawmi dan lima madrasah Alia. Temuan mengungkapkan bahwa Madrasah Qawmi tidak memiliki lingkungan belajar bahasa Inggris yang kondusif untuk tingkat kelas 8, durasi dan jadwal kelas, gaji guru, serta sumber daya, ditemukan tidak memadai dibandingkan dengan sekolah agama Alia. Berbeda dengan Madrasah Qawmi (seminari Islam Mandiri), Madrasah Alia (madrasah yang direformasi) sejauh ini memiliki keistimewaan. Orang yang diwawancarai melaporkan perlunya segera pelatihan guru dalam pembelajaran bahasa Inggris untuk sekolah agama Qawmi. Selain itu, siswa di sekolah Qawmi juga mengklaim bahwa sumber daya yang digunakan di kelas, seperti buku teks bahasa Inggris harus digunakan dengan lebih efektif. Penelitian ini juga menemukan bahwa faktor internal dan eksternal memaksa mereka untuk memasukkan mata pelajaran sekuler, khususnya bahasa Inggris dalam silabus mereka. Studi sebelumnya berfokus terutama pada sekolah agama melalui lensa sosiologis. Namun, penelitian ini membahas subjek sekuler, pengajaran bahasa Inggris di sekolah agama unsecular di Bangladesh; karenanya, ini memberikan nilai bagi pembaca, peneliti dan mereka yang terlibat dalam studi masa depan negara ini.How to Cite: Golam, A. Md. (2020). A Critical Investigation of English Subject Teaching at Two Types of Madrasas In Bangladesh. TARBIYA: Journal of Education in Muslim Society, 7(1), 1-15. doi:10.15408/tjems.v7i1.13041.